2017
DOI: 10.1002/hipo.22815
|View full text |Cite
|
Sign up to set email alerts
|

Anterior thalamic nuclei lesions have a greater impact than mammillothalamic tract lesions on the extended hippocampal system

Abstract: The anterior thalamic nuclei (ATN), mammillary bodies and their interconnecting fiber tract, the mammillothalamic tract (MTT), are important components of an extended hippocampal circuit for episodic memory. In humans, damage to the MTT or ATN in many disorders is associated with severe anterograde amnesia and it is assumed that their influence on memory is functionally equivalent. The relative influence of these two structures on memory has not, however, been assessed explicitly. Here, a direct comparison fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 63 publications
(138 reference statements)
6
36
0
Order By: Relevance
“…The mammillary bodies (MB) receive HF efferents via the postcommissural fornix and provide a unique unidirectional projection to the ATN via the mammillothalamic tract (MTT). Extensive rodent experimental lesion work supports a functional role of the ATN on the structure and function of cortical regions in the system (Aggleton, ; Dalrymple‐Alford et al, ; Perry et al, ; Savage et al, ; Vann & Nelson, ; Zhang et al, ). Clinical studies have also demonstrated the role of these diencephalic and cortical structures, including the ATN, in patients with anterograde amnesia, Alzheimer's disease and other neurodegenerative dementias (Aggleton et al, ; Carlesimo et al, ; Dzieciol et al, ; Harding et al, ; Kopelman, Tsivilis et al, ) [Color figure can be viewed at http://wileyonlinelibrary.com]…”
Section: Optogenetics To Improve Memory In Neurological Conditionsmentioning
confidence: 96%
See 2 more Smart Citations
“…The mammillary bodies (MB) receive HF efferents via the postcommissural fornix and provide a unique unidirectional projection to the ATN via the mammillothalamic tract (MTT). Extensive rodent experimental lesion work supports a functional role of the ATN on the structure and function of cortical regions in the system (Aggleton, ; Dalrymple‐Alford et al, ; Perry et al, ; Savage et al, ; Vann & Nelson, ; Zhang et al, ). Clinical studies have also demonstrated the role of these diencephalic and cortical structures, including the ATN, in patients with anterograde amnesia, Alzheimer's disease and other neurodegenerative dementias (Aggleton et al, ; Carlesimo et al, ; Dzieciol et al, ; Harding et al, ; Kopelman, Tsivilis et al, ) [Color figure can be viewed at http://wileyonlinelibrary.com]…”
Section: Optogenetics To Improve Memory In Neurological Conditionsmentioning
confidence: 96%
“…While animal evidence shows that damage to any constituent structure of the extended circuit results in memory deficits, it is clear that the ATN plays a pivotal role by influencing the functional integrity of the system (Aggleton, ; Aggleton & Nelson, ; Dalrymple‐Alford et al, ; Perry, Mercer, Barnett, Lee, & Dalrymple‐Alford, ; Savage, Hall, & Vetreno, ; Vann, ; Vann & Nelson, ; Zhang, Hu, Wu, Zhang, & Zhang, ). Furthermore, oscillatory rhythmic activity is observed throughout this network (Tsanov & O'Mara, ).…”
Section: Optogenetics To Improve Memory In Neurological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We should have explicitly stated that five of our rats had 100% bilateral MTT lesions after assessing the luxol blue stain, while four other rats with acceptable lesions had a bilateral minima of 89, 96, 99, and 99% injury; five other rats were discarded that had primarily unilateral lesions. We found that the included MTT lesions produced a reduction in relative neuronal cell counts in all three subregions of the MB; this effect was greater than that produced by our far smaller percentage-size lesions made in the ATN (Perry et al, 2018, Figure 6). These changes in the MB are expected from anatomical studies of the MTT (Cruce, 1975;Guillery, 1957;Seki & Zyo, 1984), but is a potential difference from Vann and colleagues' MTT lesions, which may leave efferents of the lateral MB unaffected (Vann & Albasser, 2009).…”
Section: Dear Editormentioning
confidence: 53%
“…We thank Vann and Nelson (2018) for providing the opportunity for further discussion on our paper, "Anterior thalamic nuclei (ATN) lesions have a greater impact than mammillothalamic tract (MTT) lesions on the extended hippocampal system", by Perry, Mercer, Barnett, Lee and Dalrymple-Alford (2018). We contend that our findings addressed important unexplored questions concerning the effects of ATN lesions and MTT lesions.…”
Section: Dear Editormentioning
confidence: 88%